Plan de Comercialización para el Hospital Veterinario César Augusto Guerrero de la Empresa Pública “La Nacional de Loja-EP”. - González Gordillo, Alex Fabián (2024)
The César Augusto Guerrero Veterinary Hospital faces challenges in the development of marketing strategies due to a lack of understanding in business management and ineffectiveness in commercial direction. It is crucial to implement concrete measures to increase effectiveness in sales and improve its position in the market. In this context, the objective of this research project is to create a Marketing Plan for the César Augusto Guerrero Veterinary Hospital of the Public Company 'La Nacional de Loja-EP.' This will be achieved through strategies and tactics designed to optimize the commercial pathway and enhance the corporate image of the Veterinary Hospital. This research project employs a quantitative approach, applies a deductive method, and implements an exploratory, descriptive, and cross-sectional research design. The study is focused on the university community and families residing in the urban area of Loja city. A total of 374 surveys were conducted among the university community, while 382 surveys were distributed to urban families in Loja using a structured survey method and random probabilistic sampling technique. This research project is descriptive and crosssectional. For data analysis, the SPSS program is employed, showing that 18.58% of the university community uses the veterinary hospital services, while 23.18% of families in Loja are aware of the veterinary hospital. Consequently, a PESTEL situational diagnosis was conducted. Analysis of the 7 Ps, and examination of Porters 5 forces were conducted, offering vital insights for the implementation of EFE, EFI, SWOT, and ANSOFF matrices. To conclude, this research project proposes strategies and tactics for marketing, focusing on digital marketing, to enhance the market position and customer loyalty of the veterinary hospita